An evaluation of multipass narrow gap laser welding as a candidate process for the manufacture of nuclear pressure vessels. (November 2017) - Feng, J.C.; Rathod, D.W.; Roy, M.J.; Francis, J.A.; Guo, W.; Irvine, N.M.; Vasileiou, A.N.; Sun, Y.L.; Smith, M.C.; Li, L.
Abstract: Nuclear pressure vessels are currently fabricated using arc welding processes. Recently, considerable effort has been directed at the development of electron beam welding as an alternative fabrication technique owing to the substantial productivity gains it would offer. However, little attention has been directed at laser-based techniques. In this work we evaluate the potential for applying multipass narrow-gap laser welding (NGLW) to the fabrication of nuclear pressure vessels, based on the characterization of a 30 mm thick weld in SA508 steel. Although still a multipass process, the number of passes is reduced in comparison to an arc weld of the same thickness, and the deposition of successive passes provides a degree of tempering to previously deposited weld metal in a way that the electron beam welding process does not. Principal engineering challenges for the implementation of multipass NGLW include the achievement of appropriate joint fit-up, and the shielding of a molten pool at the base of a deep and narrow weld groove. Highlights: Multipass narrow-gap laser welding was evaluated for 30 mm thick SA508 steel. Peak longitudinal tensile residual stresses decreased to ∼150 MPa post heat treatment. CVN, tensile properties and hardness of weld region were assessed post heat treatment. Potential process benefits are diminished compared to pressure electron beam welding.